Zoning Mashhad Watershed for Artificial Recharge of Underground Aquifers using TOPSIS Model and GIS Technique (Global Journal of Human-Social Science, 2015)
In recent years, coincide with population growth and industrial expansion, in many countries in the world,Extract water of underground sources expanded and annual withdrawal of ground water is higher than the annual feeding. This means extracting and using the water in layers that has been saved over thousands of years in the underground. Consequently groundwater levels in the area will be extracted every day and eventually drop where the water will not exist. While proper management and control of these resources will eliminate the problems of drop in water level. One way to managing groundwater resources is artificial recharge of groundwater and determine suitable locations for these purpose. growth and development trend of Mashhad city and excessive Extracting of ground water in recent years, has been essential groundwater resources management strategy in the region more than ever implied. The purpose of this study is Zoning Mashhad watershed for artificial recharge of underground aquifers using TOPSIS Model and GIS technique. TOPSIS algorithm is a Multi Criteria Decision Making, a type of compensatory model and an adaptable subgroup with strong ability to solve multi alternative problems because of having ability to overlap indicators in weak and power points.
Keywords: groundwater; aquifer; algorithm TOPSIS; artificial recharge; zoning; Watershed Mashhad